Proteasome α6 Subunit Negatively Regulates the JAK/STAT Pathway and Blood Cell Activation in Drosophila melanogaster - Järvelä-Stölting, Mirva; Vesala, Laura; Maasdorp, Matthew K.; Ciantar, Joanna; Rämet, Mika; Valanne, Susanna (Frontiers in Immunology, 2021)
JAK/STAT signaling regulates central biological functions such as development, cell differentiation and immune responses. In Drosophila, misregulated JAK/STAT signaling in blood cells (hemocytes) induces their aberrant activation. Using mass spectrometry to analyze proteins associated with a negative regulator of the JAK/STAT pathway, and by performing a genome-wide RNAi screen, we identified several components of the proteasome complex as negative regulators of JAK/STAT signaling in Drosophila. A selected proteasome component, Prosα6, was studied further. In S2 cells, Prosα6 silencing decreased the amount of the known negative regulator of the pathway, ET, leading to enhanced expression of a JAK/STAT pathway reporter gene. Silencing of Prosα6 in vivo resulted in activation of the JAK/STAT pathway, leading to the formation of lamellocytes, a specific hemocyte type indicative of hemocyte activation. This hemocyte phenotype could be partially rescued by simultaneous knockdown of either the Drosophila STAT transcription factor, or MAPKK in the JNK-pathway. Our results suggest a role for the proteasome complex components in the JAK/STAT pathway in Drosophila blood cells both in vitro and in vivo.